The Hysteretic Behavior of Partially Pre-Stressed Beam-Column Joint Sub-assemblages Made of Reactive Powder Concrete - Siti Aisyah Nurjannah; Bambang Budiono; Iswandi Imran; Saptahari Sugiri (Institute for Research and Community Services, Institut Teknologi Bandung, 2016)
Reactive powder concrete (RPC) is an alternative to normal concrete (NC) allowing for significantly higher strength of partially pre-stressed concrete structures. In the Indonesian national standard SNI 03-2847-2013 (2013) and the American standard ACI 318-14 (2014), the partial pre-stressed ratio (PPR) is limited to a maximum of 25.0 percent to ensure that pre-stressed concrete structures remain ductile and capable to dissipate seismic energy sufficiently. The objective of this experimental study was to investigate the hysteretic performance of partially pre-stressed-RPC (PP-RPC) for both interior and exterior beam-column joint sub-assemblages. Four specimens with different levels of PPR were tested with a combination of constant axial compression and cyclic lateral loads. The PPR used for the first and the second two specimens were 22.8% and 33.8%, respectively. The strength of the RPC was 101.60 MPa for all specimens. The results showed that increasing the PPR of PP-RPC improves its hysteretic performance. The best performing specimen, with a PPR of 33.8%, had a ductility that was 1.97 times that of the specimen with a PPR of 22.8%.